Ebb and Flow: A Multiple Streams Analysis of Change in Kansas Domestic Violence Policy - Bell-Sepulveda, Emily (2015)
State domestic violence legislative interventions shape the way states define and respond to domestic violence. In 2010, Kansas Governor Mark Parkinson signed into law Substitute House Bill 2517, which included a strategy to track domestic violence offenders from the time of arrest through the court system, and an expansion of the statutory definition of domestic violence. The following policy analysis uses a multiple streams framework to examine this policy change, including the motivations and actions of key policy entrepreneurs. We also discuss the implementation of the bill as passed and implications for domestic violence victims and policy activists in other states